Drosophila telomeric retrotransposons derived from an ancestral element that was recruited to replace telomerase - Villasante, Alfredo; Abad, José P.; Planelló, Rosario; Méndez-Lago, María; Celniker, Susan E.; de Pablos, Beatriz (Genome Research, 2007)
Drosophila telomeres do not have arrays of simple telomerase-generated G-rich repeats. Instead, Drosophila maintains its telomeres by occasional transposition of specific non-long terminal repeat (non-LTR) retrotransposons to chromosome ends. The genus Drosophila provides a superb model system for comparative telomere analysis. Here we present an evolutionary study of Drosophila telomeric elements to ascertain the significance of telomeric retrotransposons (TRs) in the maintenance of Drosophila telomeres. PCR and in silico surveys in the sibling species of Drosophila melanogaster and in more distantly related species show that multiple TRs maintain telomeres in Drosophila. In addition to TRs with two open reading frames (ORFs) capable of autonomous transposition, there are deleted telomeric retrotransposons that have lost their ORF2, which we refer to as half telomeric-retrotransposons (HTRs). The phylogenetic relationship among these telomeric elements is congruent with the phylogeny of the species, suggesting that they have been vertically inherited from a common ancestor. Our results suggest that an existing non-LTR retrotransposon was recruited to perform the cellular function of telomere maintenance.